Bkaʼbrgyud gser ʼphreṅ : a golden rosary of lives of eminent Bkaʼ-brgyud-pa masters (Topden Tshering ; distributor, Tibetan Bonpo Monastic Centre, 1975)
Hagiographies of the early masters of the Kargyudpa tradition from Vajradhāra through Sgam-po-pa Bsodnams-rin-chen, 1079-1153.